New Student Online Registration Site Usage Training - Wahyu Sindu Prasetya; Aurea Firanda Khatami; Hariyanti Hariyanti (STMIK Pontianak, 2020)
The online student registration information system is seen as very important in this era of digitalization. What's more, there is the convenience and efficiency that is obtained when registering online. The problem of time, distance and place is no longer an obstacle in registering on time. Therefore, this service aims to provide an understanding of the online admissions information system at SMA Negeri 1 Sejangkung. This community service workshop was attended by 20 people consisting of teachers and students from SMA Negeri 1 Sejangkung. This training workshop was carried out using a system demonstration method, lectures, discussions with participants and questions and answers. This training workshop provides information to teachers and students at SMA Negeri 1 Sejangkung about the importance of an online registration system to facilitate the student registration process, which no longer has to be face-to-face or come directly to school.